Imaging Findings and Clinical Features of Primary Spinal Epithelioid Hemangioendothelioma - Liang, Pan; Zhu, Bing-Bing; Ren, Xiu-Chun; Gao, Jian-Bo (Frontiers in Oncology, 2022)
Rationale and Objectives: Primary spinal epithelioid hemangioendothelioma (SEHE) is an extremely rare angiocentric vascular neoplasm with inherent metastatic potential, which pursued a clinical course intermediate between hemangioma and angiosarcoma. The present study sought to present computed tomography (CT) and magnetic resonance imaging (MRI) findings and clinical features of primary SEHE and review the literature. Materials and Methods: Clinical data of four patients with primary SEHE confirmed by pathology from January 2011 to May 2020 were analyzed retrospectively. Two cases underwent CT scan, while 3 cases underwent MRI scan. Image observation included the tumor location, bone changes, morphology, density/signal characteristics, and enhanced features. Results: The four patients were all female who ranged in age from 25 to 74 years. Four cases of the lesions were in the vertebral body, among them, two cases involved the accessory of the vertebra. Soap bubble appearance was detected in 2 cases, honeycomb osteolytic appearance in 2 cases, the sclerotic margin in 3 cases, and accompanied vertebral compression fracture in 1 case. CT showed slightly inhomogeneous low density, with punctate high-density foci. MRI showed an inhomogeneous low signal on T1WI and a high signal on T2WI. Contrast-enhanced CT/MRI demonstrated moderate to intensive inhomogeneous enhancement of the lesions. The discs were normal. In one case lesions presented dural tail sign. Conclusions: Primary spinal EHE is so rare in clinic as an aggressive vascular tumor. The relatively typical clinical features and radiographic findings can help for preoperative diagnosis.